Bioinformatics approaches for viral metagenomics in plants using short RNAs: model case of study and application to a Cicer arietinum population - Pirovano, Walter; Miozzi, Laura; Boetzer, Marten; Pantaleo, Vitantonio (Frontiers in Microbiology, 2015)
Over the past years deep sequencing experiments have opened novel doors to reconstruct viral populations in a high-throughput and cost-effective manner. Currently a substantial number of studies have been performed which employ Next Generation Sequencing (NGS) techniques to either analyze known viruses by means of a reference-guided approach or to discover novel viruses using a de novo-based strategy. Taking advantage of the well-known Cymbidium ringspot virus we have carried out a comparison of different bioinformatics tools to reconstruct the viral genome based on 21-27 nt short (s)RNA sequencing with the aim to identify the most efficient pipeline. The same approach was applied to a population of plants constituting an ancient variety of Cicer arietinum with red seeds. Among the discovered viruses, we describe the presence of a Tobamovirus referring to the Tomato mottle mosaic virus (NC_022230), which was not yet observed on C. arietinum nor revealed in Europe and a virod referring to Hop stunt viroid (NC_001351.1) never reported in chickpea. Notably, a reference sequence guided approach appeared the most efficient in such kind of investigation. Instead, the de novo assembly reached a non-appreciable coverage although the most prominent viral species could still be identified. Advantages and limitations of viral metagenomics analysis using sRNAs are discussed.